(untitled) (Colloquia Comparativa Litterarum, 2025)
The paper analyses two film adaptations (1977, 2020) of Romain Gary’s novel The Life Before Us exploring the transformation strategies originating from the transition from page to screen as well as different forms of (re)contextualisation in the 20th and 21st century. The comparative case study examines the evolution of dominant adaptation approaches going from fidelity to the source text to intertextuality and reinvention. We aim to reveal the relevance of the author’s humanist views through the strong visual thematisation of universal values and empathic figures’ interactions.